Transfer Assessment of Carbendazim Residues from Rape Flowers to Apicultural Products - Ying-Hong Li; Bei-Lei Zhou; Ming-Rong Qian; Qiang Wang; Hu Zhang (Journal of Analytical Methods in Chemistry)
Carbendazim is usually used to control the Sclerotinia sclerotiorum of rapes during the flowering period. This paper presents a study on transfer assessment of carbendazim residues from rape flowers to apicultural products. In the field trials, the rapes were sprayed with carbendazim on standard dosage. Bees produced apicultural products (bee pollen, honey, and royal jelly) from sprayed rapes. Apicultural products were collected on a regular basis. Carbendazim residues were extracted from bee pollen, honey, and royal jelly, respectively. HPLC/ESI-MS/MS method was developed and partially validated to identify and quantify carbendazim residues. The limits of quantification in pollen, honey, and royal jelly were 0.01 mg/kg. Mathematical curve fitting was carried out on the basis of transfer assessment of carbendazim residues from rape flowers to apicultural products. The respective carbendazim residues were 1.10±0.03 mg/kg in pollen on 18th day, 0.032±0.001 mg/kg in honey on 24th day, and 0.077±0.002 mg/kg in royal jelly on 22nd day. Transfer assessment and mathematical curve fitting of carbendazim residues from rape flowers to apicultural products show carbendazim diminished over spraying time. The gap of carbendazim residues between pollen and honey is decreased with time. The carbendazim residues in pollen are 10 times higher than that of honey and jelly.